Tetrahydroisoquinoline and [Beta]-Carboline alkaloids from Haloxylon articulatum (Cav.) Bunge (Chenopodiaceae) - El-Shazly, Assem; Wink, Michael (Zeitschrift für Naturforschung. C, a journal of biosciences, 2014)
Salsolidine and 2-methyl,1,2,3,4-tetrahydro-β-carboline were isolated from Haloxylon articulatum (growing in Egypt) besides the known carnegine and N-methylisosalsoline. 2- methyl,1,2,3,4-tetrahydro-β-carboline was recorded for the first time in the genus Haloxylon. The alkaloids were identified by spectroscopic methods (MS, 1D and 2D NMR).